PERAN PERUBAHAN LABA DALAM MEMEDIASI PENGARUH CURRENT RATIO (CR), TOTAL ASSET TURNOVER (TATO), DAN TINGKAT INFLASI TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR TRANSPORTASI DAN LOGISTIK PERIODE 2020-2022 - Dewi, Rana Hariantika; Wahyuni, Ika; Pramitasari, Triska Dewi (Fakultas Ekonomi dan Bisnis, 2024)
The purpose of a company being established is to make a profit. However, in maintaining the company and in earning profits depends on how financial management manages the company's finances. To earn profits, companies need to have efficient and effective financial performance because it is important for all companies in maintaining their business. Companies in the field of transportation and logistics are companies that provide transportation facilities and infrastructure to facilitate the distribution of logistics to regions, both land, sea and air transportation. The purpose of this study was to analyze and test the role of earnings changes in mediating the effect of Current Ratio (CR), Total Asset Turnover (TATO), and Inflation rate on stock prices. The population in this study was the Transportation and Logistics Sector with 37 companies with a sample of 10 companies. The sampling technique was purposive sampling technique. Data analysis and hypothesis testing using Structural Equation Analysis - Partial Least Square (PLS-SEM). The results of research hypothesis testing using the Smart PLS 3. 0, shows that Current Ratio (CR) and Inflation rate has a negative and insignificant effect on profit changes, Total Asset Turnover (TATO) has a positive and insignificant effect on profit changes, Current Ratio (CR) and Inflation rate has a negative and insignificant effect on stock price, Total Asset Turnover (TATO) and Profit change has a positive and insignificant effect on stock price, Current Ratio (CR) on stock price through profit change has a negative and insignificant effect, Total Asset Turnover (TATO) on stock price through profit change has a positive and insignificant effect, inflation rate on stock price through profit change has a negative and insignificant effect.